Strategi Dakwah Majelis Dzikir dan Sholawat El Muhibbin dalam Menyebarkan Pesan Dakwah melalui Kesenian Hadrah pada Masyarakat Kelurahan Baratan Kecamatan Patrang Kabupaten Jember - Abdul Fatah Ark; Ahidul Asror (Icon: Islamic Communication and Contemporary Media Studies, 2022)
Da'wah is the process of conveying Islamic values ​​in order to change the behavior of Muslims to be better. The interpretation of da'wah in society is the process of conveying messages that contain religious values ​​with various methods. In the delivery of da'wah there are two important things to note, namely the da'wah strategy (planning activities before carrying out da'wah) and da'wah methods (techniques used in delivering da'wah). This study connects two variables, namely the Da'wah Strategy and the Arts. The focus of the research is "First, to find out what are the da'wah messages contained in the art of hadroh carried out by the Council of Dhikr and Sholawat El Muhibbin, Second. To find out how the technique of delivering da'wah messages is carried out by the Council of Dhikr and Sholawat El Muhibbin". The purpose of this research is “to know the message of da'wah contained in the art of hadroh used by the Council of Dhikr and Sholawat El Muhibbin”.